Tantangan dan Kendala Pengendalian African Swine Fever - Roza Azizah Primatika; Etih Sudarnika; Bambang Sumiarto; Chaerul Basri (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2021)
African Swine Fever (ASF) is a highly contagious hemorrhagic viral disease that attacks pigs and wild pigs causing economic losses for farms small and large scale. ASF outbreaks that occurred in several regions in the world have caused unrest for the livestock sector. The rapid spread of the ASF virus has resulted in very high pig mortality. ASF virus transmission can occur through direct or indirect contact. Urine and faecal excretion of pigs is an important route of ASF transmission. The ASF virus has three transmission cycles, namely the silvatic, domestic and wild boar cycles. Outbreaks that occur in several countries encourage the strategy of controlling and overcoming the disease through surveillance. ASF disease control that has been carried out includes improving farm biosecurity management systems and limiting the movement of animals and animal products before the ASF vaccine is found.